"IDEA OF THE UNITY OF MANKIND" OF V. VERNADSKY’S CONCEPTION OF NOOSPHEREGENESIS IN THE CONTEXT OF PHILOSOPHICAL DISCOURSE OF THE TWENTIETH CENTURY - Vilkov, V.; Pogorily, A. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
The article presents an analysis of the main epistemological, philosophical, political and ideological commitments of the V. Vernadsky’s interpretation of the "idea of the unity of mankind"